2004
DOI: 10.1159/000080348
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Renal Tubules at the Interface of an Artificial Interstitium

Abstract: During kidney development a multitude of tubular portions is formed. Little knowledge is available by which cellbiological mechanism a cluster of embryonic cells is able to generate the threedimensional structure of a tubule. However, this know-how is most important in tissue engineering approaches such as the generation of an artificial kidney module or for the therapy of renal diseases using stem cells. To obtain cellbiological insights in parenchyme development we elaborate a new technique to generate under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…7c). 19 Thus, label for collagen type III is missing in the zone of renal stem/progenitor cells, but it is co-localized with laminin c1 in the maturing zone along the shaft of the collecting duct ampulla. In consequence, the experiments clearly show that collagen type III is not the primary skeletonal element of the interstitium in developing renal parenchyma.…”
Section: Arise Of Structural Elements In the Interstitiummentioning
confidence: 97%
See 3 more Smart Citations
“…7c). 19 Thus, label for collagen type III is missing in the zone of renal stem/progenitor cells, but it is co-localized with laminin c1 in the maturing zone along the shaft of the collecting duct ampulla. In consequence, the experiments clearly show that collagen type III is not the primary skeletonal element of the interstitium in developing renal parenchyma.…”
Section: Arise Of Structural Elements In the Interstitiummentioning
confidence: 97%
“…For soybean agglutinin-labeling (SBA, Vector, Burlingame, USA) the samples were exposed to fluorescein-isothiocyanate (FITC)-conjugated lectin diluted 1:2000 in blocking solution for 45 min as earlier described. 18 For immunohistochemical label monoclonal antibodies such as mab anti-laminin c1 (kindly provided by Dr. L. Sorokin, Lund, Sweden), 19 mab anti-P CD Amp 1, 27 mab anti-Na/K-ATPase alpha 5 (Developmental Studies Hybridoma Bank, Iowa City, USA) and mab anti-collagen type III (III-53, Calbiochem, Schwalbach, Germany) was applied in blocking solution. After washing with phosphatebuffered saline (PBS) containing 1% bovine serum albumin (BSA), the specimens were then incubated for 45 min with donkey-anti-mouse-IgG-fluoresceinisothiocyanate (FITC) or goat-anti-rat-IgG-rhodamine (Jackson Immunoresearch Laboratories, West Grove, USA) diluted 1:50 in this solution.…”
Section: Histochemical Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous publications of our group proved the feasibility of generating tubules derived from renal stem/progenitor cells at the interface of an artificial interstitium made of a polyester fleece within a perfusion culture container [18,19]. We found that the generation of renal tubules depends specifically on the presence of aldosterone.…”
Section: Introductionmentioning
confidence: 51%